2013
DOI: 10.1063/1.4804264
|View full text |Cite
|
Sign up to set email alerts
|

Growth, microstructure, and luminescent properties of direct-bandgap InAlP on relaxed InGaAs on GaAs substrates

Abstract: Articles you may be interested inEffects of doping and grading slope on surface and structure of metamorphic InGaAs buffers on GaAs substrates Direct-bandgap InAlP alloy has the potential to be an active material in nitride-free yellow-green and amber optoelectronics with applications in solid-state lighting, display devices, and multi-junction solar cells. We report on the growth of high-quality direct-bandgap InAlP on relaxed InGaAs graded buffers with low threading dislocation densities. Structural characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Color contrast stripes weakly visible within the active layer are attributed to composition modulation of the Al x In 1-x P film. 26 Figure 1(c) shows representative transmission electron diffraction (TED) images from each cladding layer and from the active region of the device. The superspots visible in the active region TED image indicate the presence of both variants of CuPt-B ordering.…”
Section: Resultsmentioning
confidence: 99%
“…Color contrast stripes weakly visible within the active layer are attributed to composition modulation of the Al x In 1-x P film. 26 Figure 1(c) shows representative transmission electron diffraction (TED) images from each cladding layer and from the active region of the device. The superspots visible in the active region TED image indicate the presence of both variants of CuPt-B ordering.…”
Section: Resultsmentioning
confidence: 99%
“…12,13 The lack of atomic ordering was verified using transmission electron diffraction measurements in a transmission electron microscope (TEM). A more complete discussion of the growth of Al x In 1Àx P using the above described method, along with TEM images of the graded buffer layers and disordered Al x In 1Àx P material, can be found in Mukherjee et al 11 All Al x In 1Àx P epi-layers are nominally 700 nm thick and are observed to be pseudomorphically strained to the In y Ga 1Ày As buffer layer based on XRD reciprocal space mapping. Samples discussed in this article are all compressively strained to the In y Ga 1Ày As, where the strain in all cases is less than 0.37%.…”
Section: Methodsmentioning
confidence: 99%
“…A set of bulk Al x In 1Àx P samples closely lattice matched to InGaAs graded buffer layers were grown on GaAs substrates using MOCVD. 11 Simultaneous observation of direct and indirect transitions by photoluminescence (PL) yields a precise value of x c ¼ 40.5% at low temperatures in completely disordered alloys at low temperature. Implications for the use of direct bandgap Al x In 1Àx P alloys in solid-state lighting applications are also discussed.…”
mentioning
confidence: 99%
“…Prior work on direct band gap AlInP in the same growth chamber showed no increase in oxygen incorporation as the growth temperature was lowered from 725 °C to 620 °C. 28 However, if continues to rise from a further increase in electron-hole separation due to the formation of larger ordered domains at 625 °C, it could become comparable to and result in a lowering of the emission intensity. In previous work on ordered AlGaInP quantum wells, which are known to have a higher order parameter than GaInP, was seen to increase by nearly an order of magnitude at room temperature compared to the disordered case.…”
Section: A Luminescence Away From Dislocationsmentioning
confidence: 99%